Differential effects of clary sage (Salvia sclarea L.) oil and linalyl acetate on depression levels in diabetic foot ulcer patients with T2DM: a randomized blinded controlled trial - Ji Won Son; Purum Kang; Sun Seek Min; Geun Hee Seol; Geun Hee Seol (Frontiers in Medicine)
BackgroundDiabetic foot ulcer (DFU) is a significant global health concern due to its substantial burden on individuals and healthcare systems. In addition to its physical impact, DFU has emotional effects on patients. This study analyzed the effects of inhaling clary sage (CS; Salvia sclarea L.) or linalyl acetate (LA) on depression and psychological factors in patients with DFU.MethodsThis study, performed at the Diabetic Wound Center, enrolled DFU patients, categorized as having mild or moderate to severe depression based on visual analog scale (VAS) for depression scores. Patients were randomized to inhalation of 5% CS oil, 5% LA or almond oil (control) by natural breathing. Blood pressure, heart rate, Depression-VAS, Anxiety-VAS, and Stress-VAS were measured before and after inhalation.ResultsThis study enrolled 72 patients with DFU, including 43 with mild and 29 with moderate to severe depression. Of the 43 patients with mild depression, 14, 14, and 15 were randomized to inhalation of CS, LA, and almond oil, respectively. Of the 29 patients with moderate to severe depression, 9, 11, and 9 were randomized to inhalation of CS, LA, and almond oil, respectively. Compared with inhalation of almond oil, inhalation of CS oil significantly reduced stress (p < 0.05) and (p < 0.01) in patients with mild depression, whereas inhalation of LA significantly reduced anxiety-VAS (p < 0.05) and depression-VAS (p < 0.05) in patients with moderate to severe depression.ConclusionInhalation of CS oil may have the potential to alleviate stress and anxiety in DFU patients with mild depression, whereas inhalation of LA may have the potential to alleviate anxiety and depression in DFU patients with moderate to severe depression. These findings suggest that adjunct therapy in DFU patients should be individualized according to the degree of depression.Clinical trial registrationhttp://cris.nih.go.kr/, identifier KCT0009722.